PENGUATAN KARAKTER BERNALAR KRITIS MELALUI PROBLEM BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Nur Kholifah, Yuni; Putri Maharani, Amanda; Lorenza Abadi, Deeva; Jarisma, Dinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical reasoning is a primary focus in the implementation of the Kurikulum Merdeka (Independent Curriculum), particularly in elementary school mathematics instruction. Problem-Based Learning (PBL) stands out as an effective model for developing this trait. This article aims to analyze the role of PBL in strengthening the critical reasoning character of elementary school students through a literature review. The study examines scholarly articles, research findings, and education policy documents published between 2021 and 2026. The findings indicate that PBL enhances critical thinking, problem-solving skills, active learning engagement, and the ability to construct logical arguments through contextualized learning activities. Furthermore, the implementation of PBL aligns with the critical reasoning dimension of the Profil Pelajar Pancasila (Pancasila Student Profile). Consequently, PBL serves as an effective instructional model and strategy for strengthening the critical reasoning character of elementary school students in mathematics education.